Effect of the specific thromboxane receptor blocking drug AH23848 in patients with angina pectoris. Issue 6 (December 1986) - De Bono, D P; Lumley, P; Been, M; Keery, R; Ince, S E; Woodings, D F
Abstract : The effect of the specific thromboxane receptor blocking drug AH23848 was investigated in two double blind placebo controlled studies in male patients with exercise induced angina pectoris and angiographically verified coronary lesions. In the first study cardiac pacing was performed in twenty patients after coronary angiography. Patients were then randomised into two groups and received either AH23848 (70 mg orally) or placebo. One hour later cardiac pacing was repeated. Neither treatment had any significant effect upon time to angina or the rate-pressure product at the onset of chest pain in these patients. In the second study twenty male patients were randomised to seven days' treatment with AH23848 (70 mg three times a day) or placebo followed by a crossover to the other treatment for a further seven days. Clinical assessment was performed before treatment and at the end of each treatment period. There was no significant difference between the placebo and AH23848 treatment periods in exercise tolerance, the rate-pressure product at angina after exercise testing, the number of ischaemic attacks as determined from 24 hour ambulatory electrocardiograms, the number of attacks of pain, or the number of glyceryl trinitrate tablets consumed. This lack of a clinical effect with AH23848 was seen despite a profound inhibition of ex vivo platelet aggregation stimulated by the thromboxane A2-mimetic U-46619. Because in experimental animals in vivo AH23848 blocks vascular thromboxane receptors as well as platelet thromboxane receptors the lack of effect of AH23848 in cardiac pacing and exercise induced angina is unlikely to be the result of inadequate blockade of thromboxane receptors. The lack of effect of the drug is more likely to indicate that thromboxane A2, is not a factor in the aetiology of the pain experienced by these patients during exercise or cardiac pacing.